UNDERSTANDING THREATS TO SPACE SYSTEMS AND SPACE ASSETS strategic challenges in the new space... environment. - PRAK, JAKUB (ROUTLEDGE, 2026)
This book explores the current space threat profile in an increasingly contested, congested, and competitive space environment.This work looks at the conflictual nature of space relations and highlights various issues resulting from greatpower competition in the space domain. This book recognizes nonstate entities' increased engagement in this domain, including their different roles, and consequently incorporates commercial actors into space strategic thinking. It also discusses the perils of the space environment, political conflicts, space weapons, malicious space operations, and the risks stemming from potentially hazardous dualse technology. Finally, this book outlines the means to improve the protection of space systems with an emphasis on the inclusion of a broad spectrum of stakeholders and offers arguments for the establishment of new norms to strengthen the responsible use of outer space. This book will be of much interest to students of space power, security studies, and international relations.